2020
DOI: 10.3389/fendo.2019.00844
|View full text |Cite
|
Sign up to set email alerts
|

Can Dietary Intake of Vitamin C-Oriented Foods Reduce the Risk of Osteoporosis, Fracture, and BMD Loss? Systematic Review With Meta-Analyses of Recent Studies

Abstract: Background: Several epidemiological studies have been performed to evaluate the association of dietary intake of vitamin C-oriented foods (DIVCF) with risk of fracture and bone mineral density (BMD) loss, but the results remain controversial. Therefore, we conducted a systematic meta-analysis to assess this correlation. Methods: We searched EmBase, PubMed, Web of Science, and the Chinese database CNKI for relevant articles published up to August 2019. Pooled relative risks (RRs) with 95% confidence intervals (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“…Serum VC concentration has been shown to correlate with low energy fracture risk [52,65] and BMD level [61,65,67], but lack of correlation was reported, too [64,67]. A positive impact of dietary VC intake on BMD may be confirmed by the cumulative result obtained from the meta-analysis in which BMD at the lumbar spine (pooled r = 0.15; 95% CI, 0.09-0.23) and BMD at the femoral neck (pooled r = 0.20; 95% CI, 0.11-0.34; p < 0.05) showed beneficial effects of dietary intake of vitamin C oriented food [12]. Discrepancies between the results obtained may result, among others, from the differences in protocols of the conducted tests and the exclusion criteria used.…”
Section: Cross-sectional Studiesmentioning
confidence: 71%
See 3 more Smart Citations
“…Serum VC concentration has been shown to correlate with low energy fracture risk [52,65] and BMD level [61,65,67], but lack of correlation was reported, too [64,67]. A positive impact of dietary VC intake on BMD may be confirmed by the cumulative result obtained from the meta-analysis in which BMD at the lumbar spine (pooled r = 0.15; 95% CI, 0.09-0.23) and BMD at the femoral neck (pooled r = 0.20; 95% CI, 0.11-0.34; p < 0.05) showed beneficial effects of dietary intake of vitamin C oriented food [12]. Discrepancies between the results obtained may result, among others, from the differences in protocols of the conducted tests and the exclusion criteria used.…”
Section: Cross-sectional Studiesmentioning
confidence: 71%
“…There are currently over 200 different forms available in the literature, the size of which ranges from 5–350 items [ 69 ]. The researchers of the presented study used forms containing 79–220 items [ 12 , 53 , 54 , 56 , 57 , 58 , 61 , 63 , 64 , 66 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 ] as well as 24-h dietary recall [ 50 , 51 , 55 , 59 , 65 , 76 ], 3–7 day diet diary [ 52 , 58 , 60 , 67 , 77 ] and other surveys dedicated to their study [ 63 ]. The diversity of the methodology used to assess the average daily dose of vitamin C may cause difficulties in comparing the results obtained.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Antioxidants present in fruits and vegetables have been highlighted as one of the key causes of beneficial outcomes for bone health [ 5 ]. Epidemiological studies have shown that BMD is positively related to the intake of vitamin C [ 38 ], vitamin E [ 8 ], carotenoids [ 6 ], and flavonoids [ 10 , 11 ] in postmenopausal women. Collectively, these observations indicated that the BMD of the femoral neck was strongly affected by the intake of antioxidants, while the BMD of the total hip and lumbar spine was slightly affected in postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%